2021
DOI: 10.3389/fendo.2021.689845
|View full text |Cite
|
Sign up to set email alerts
|

JunD Regulates Pancreatic β-Cells Function by Altering Lipid Accumulation

Abstract: The impairment of pancreatic β-cells function is partly caused by lipotoxicity, which aggravates the development of type 2 diabetes mellitus. Activator Protein 1 member JunD modulates apoptosis and oxidative stress. Recently, it has been found that JunD regulates lipid metabolism in hepatocytes and cardiomyocytes. Here, we studied the role of JunD in pancreatic β-cells. The lipotoxic effects of palmitic acid on INS-1 cells were measured, and JunD small-interfering RNA was used to assess the effect of JunD in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…This could explain the absence of well-established pancreas TFs such as MAFA (Olbrot et al 2002), MNX1 (Flanagan et al 2014), NEUROG3 (Krentz et al 2017), FOXA2 (Lee et al 2019) and NKX2-2 (Mastracci et al 2011) in this analysis. Nevertheless, in support of the validity of our findings, ATAC-seq, the literature and immunohistochemistry of human pancreas sections corroborate several pySCENIC predictions reported here such as BHLHE41, JUND and HEYL (Gomez et al 2015; Good et al 2019; K. Wang et al 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This could explain the absence of well-established pancreas TFs such as MAFA (Olbrot et al 2002), MNX1 (Flanagan et al 2014), NEUROG3 (Krentz et al 2017), FOXA2 (Lee et al 2019) and NKX2-2 (Mastracci et al 2011) in this analysis. Nevertheless, in support of the validity of our findings, ATAC-seq, the literature and immunohistochemistry of human pancreas sections corroborate several pySCENIC predictions reported here such as BHLHE41, JUND and HEYL (Gomez et al 2015; Good et al 2019; K. Wang et al 2021).…”
Section: Discussionsupporting
confidence: 92%
“…EGR1 (but not EGR4) has been shown to transcriptionally regulate GCG (Leung-Theung-Long et al 2005) as well as the PDX1 promoter in beta cells (Eto, Kaur, and Thomas 2007). STAT4 and JUND have been described respectively in pancreatic tissue in general and in beta cells but not in alpha cells (Yu and Kim 2012; Good et al 2019; K. Wang et al 2021) (Figure 3B,C) .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…RXRA was predicted to cooperate with the bile acid receptor NR1H4 in SC-β-cell and SC-EC gene regulation ( Figure 2J ), identifying a possible mechanism for the role of bile acids in insulin secretion (Vettorazzi et al, 2016). Of interest is also the SC-β-cell-specific interaction between BACH2 and JUND ( Figure 2K ), which have both been reported to contribute to β-cell dysfunction in type 2 diabetes (Good et al, 2019; Son et al, 2021; Wang et al, 2021). In summary, our GRN provides a resource for interrogating gene regulatory mechanisms in SC-islet cell types and their precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, JUND are assigned with high weights on the models of multiple target genes, and also tend to form clockwise curve (Supplementary Figure 2c). Early studies have reported that JUND modulates cell differentiation, proliferation, and apoptosis [30], further confirming the regulation mechanisms of JUND in pancreatic cells [31,32].…”
Section: Tfvelo Can Model Cell Differentiation Process On Pancreas Da...mentioning
confidence: 64%